A Tight Leash or a Tight Spot? A Case Study on Tightness of Action Controls in a German Insurance Firm - Barbara E. Weißenberger; Amra Tica (Swiss Journal of Business)
The objective of this paper is to theoretically expand the understanding of tight management control with respect to action controls. An empirical conceptualization of tight control has so far only been available for budgeting (Van der Stede 2001). Our paper is based on a case study in the German insurance industry with 15 semi-structured interviews. Our results indicate that three of the five characteristics used to describe tight budgets can also be applied to the understanding of tight action controls: a high level of importance attached to achieving objectives, a low tolerance for deviations and intensity of communication (albeit in a broader sense). Furthermore, our results indicate that tight action controls are also perceived positively in terms of task support. The association with dysfunctional behavioral effects is thus more complex than management control literature suggests.